Benchmarking company profitability and growth: some measurement issues for small firms in Ireland - Hewitt-Dundas, Nola; Roper, Stephen (Economic & Social Studies, 1998)
International comparisons of productivity, purchasing power and inflation can depend crucially on differences in national statistical procedures. This paper indicates that even in more localised comparisons of small firm performance, differences in accounting practice can have an important distortionary effect. In particular, the tendency for small firms in Northern Ireland to under-value grant assisted asset purchases may be inflating asset based profit measures. This under-valuation is shown, however, to explain only part of the difference between the efficiency of asset utilisation in Northern Ireland and the Republic of Ireland. By contrast small firms in the Republic of Ireland had higher levels of both sales per employee and profit per employee.
Keywords: Profitability; Small firms; Corporate growth; Ireland; Northern Ireland